2009
DOI: 10.1063/1.3075897
|View full text |Cite
|
Sign up to set email alerts
|

Domain stabilization effect of interlayer on ferroelectric poly(vinylidene fluoride-trifluoroethylene) copolymer ultrathin film

Abstract: A charge injection material, poly(3,4-ethylene dioxythioohene)-poly(styrene sulfonic) acid, is introduced as a buffer layer between metal electrodes and a ferroelectric poly(vinylidene fluoride-trifluoroethylene) [P(VDF-TrFE)] copolymer ultrathin film. The buffer layer not only prevents the reactions between P(VDF-TrFE) layer and the top electrode during metallization process, which leads to the loss of polarization, but also supplies the amount of charges needed for compensation of the ferroelectric dipoles t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(43 citation statements)
references
References 17 publications
1
42
0
Order By: Relevance
“…Improved device performance with higher P r and faster switching speeds were achieved. A P r of more than 70% of its initial value can be achieved after 1×10 7 cycles of switching for 50 nm thick P(VDF-TrFE) film devices, as shown in Figure 20 [Xu et al, 2007[Xu et al, , 2009. Xu et al also found that the conducting polymer buffer layers improve the degree of crystallinity of the thin films [Xu et al, 2009].…”
Section: Contact Dependencementioning
confidence: 96%
See 4 more Smart Citations
“…Improved device performance with higher P r and faster switching speeds were achieved. A P r of more than 70% of its initial value can be achieved after 1×10 7 cycles of switching for 50 nm thick P(VDF-TrFE) film devices, as shown in Figure 20 [Xu et al, 2007[Xu et al, , 2009. Xu et al also found that the conducting polymer buffer layers improve the degree of crystallinity of the thin films [Xu et al, 2009].…”
Section: Contact Dependencementioning
confidence: 96%
“…Therefore, it allows the copolymer to crystallize into the ferroelectric phase at temperatures below the melting point. The copolymer crystal structure, phase transition behavior and ferroelectric properties are affected by the ratio of VDF/TrFE content and the synthesizing conditions [Yamada & Kitayama, 1981]. The experimental data from UT Dallas shown in this chapter are for P(VDF-TrFE) copolymer with 70/30 (VDF/TrFE), synthesized using a suspension polymerization process.…”
Section: Materials Properties Of P (Vdf-trfe) Copolymermentioning
confidence: 99%
See 3 more Smart Citations